2017
DOI: 10.3390/ijgi6070204
|View full text |Cite
|
Sign up to set email alerts
|

Disaster Hashtags in Social Media

Abstract: Social media is a rich data source for analyzing the social impact of hazard processes and human behavior in disaster situations; it is used by rescue agencies for coordination and by local governments for the distribution of official information. In this paper, we propose a method for data mining in Twitter to retrieve messages related to an event. We describe an automated process for the collection of hashtags highly related to the event and specific only to it. We compare our method with existing keyword-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 26 publications
1
27
0
2
Order By: Relevance
“…As a first step, we trained several models with topic numbers between 10 and 100 and calculated the density for each model following the approach presented by Cao, Xia, Li, Zhang, and Tang (2008) and implemented in the package ldatuning (Murzintcev, 2016). As a first step, we trained several models with topic numbers between 10 and 100 and calculated the density for each model following the approach presented by Cao, Xia, Li, Zhang, and Tang (2008) and implemented in the package ldatuning (Murzintcev, 2016).…”
Section: Topic Models-ldamentioning
confidence: 99%
See 1 more Smart Citation
“…As a first step, we trained several models with topic numbers between 10 and 100 and calculated the density for each model following the approach presented by Cao, Xia, Li, Zhang, and Tang (2008) and implemented in the package ldatuning (Murzintcev, 2016). As a first step, we trained several models with topic numbers between 10 and 100 and calculated the density for each model following the approach presented by Cao, Xia, Li, Zhang, and Tang (2008) and implemented in the package ldatuning (Murzintcev, 2016).…”
Section: Topic Models-ldamentioning
confidence: 99%
“…We thus integrate both quantitative assessment and human judgement in the steps we performed in the identification of the right model for this study. As a first step, we trained several models with topic numbers between 10 and 100 and calculated the density for each model following the approach presented by Cao, Xia, Li, Zhang, and Tang (2008) and implemented in the package ldatuning (Murzintcev, 2016). The idea of the density-based method is to identify a topic number where the similarity of terms within a topic will be maximized while keeping the similarity between topics as small as possible.…”
Section: Topic Models-ldamentioning
confidence: 99%
“…The latter study used a combination of latent Dirichlet allocation (LDA) for semantic information extraction and local spatial autocorrelation for hotspot detection. Using machine-learning methods (support vector machine, supervised latent Dirichlet allocation) in combination with several public disaster-related datasets, it was shown that a classification model of Twitter content can be trained to automatically collect hashtags highly related to the event of interest [26].…”
Section: Related Literaturementioning
confidence: 99%
“…Compared to Sina Weibo users, Twitter users prefer hashtags [20], a word or an abbreviation starting with #, which is often used to mark the topic of the microblog. Some scholars use hashtags to distinguish microblogs related to or unrelated to disasters [21,22]. In this study, # was filtered out with other special symbols, and hashtags were not used as a basis for judging emergency information, because their usage is rare in Sina Weibo.…”
Section: Datamentioning
confidence: 99%